Utilization of print media for agriculture development: A case study of peasants - Salve R. N. 2, *Sheela D. Deshmukh1, M.S. Prashanth1, (International Multidisciplinary Research Journal, 2011)
Shetkari is the print media that is focused to provide improved methods and techniques of cultivation to provide improved methods and techniques of cultivation to peasants in Western Maharashtra especially the literate, youth and commercial cultivator. Peasants are utilizing latest agricultural ideas for agricultural development. Agricultural development means economic growth along with maintaining their fertility of soil. To illustrate the role of print media, a study of Yalgund village of Kolhapur District is conducted. Case studies of big, medium marginal and large peasants are conducted to illustrate the importance of agricultural communication. It is found that big and small peasants have been applying the ideas to boots their agricultural economic into commercial profitable industry. The marginal farmer has implemented the technique of mixed cropping profitably. However, there is no utilization by the landless.